Relationship between innovation and growth of sme in the food and beverage industry of Bogota, Colombia - Díaz-Hincapié , Fernán Ignacio; Melgarejo-Molina , Zuray Andrea; Vera-Colina, Mary Analí (Universidad Pedagógica y Tecnológica de Colombia, 2021)
The objective of the work is to determine the relationship between innovation and business growth of SMEs in the food and beverage sector of the city of Bogotá (Colombia) in the period 2007-2016. To do this, an OLS estimate was made to a large and homogeneous sample of companies in this sector, using statistical information from the National Administrative Department of Statistics (2017, 2018). The results show that there is a significant and positive relationship between innovation and business growth, in which the size of the organizations is also a determining factor. As an additional contribution, this research goes beyond analyzing the traditional relationship between innovation and growth, and also considers the links of the innovative strategy with the generation of added value and with the greater productivity of the analyzed organizations, which allows reiterating the need to promote such strategies that enhance the development of the sector.